2017
DOI: 10.1186/s13567-017-0419-4
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and CCL5 driven attraction of CD172a+ monocytic cells during an equine herpesvirus type 1 (EHV-1) infection in equine nasal mucosa and the impact of two migration inhibitors, rosiglitazone (RSG) and quinacrine (QC)

Abstract: Equine herpesvirus type 1 (EHV-1) causes respiratory disease, abortion and neurological disorders in horses. Besides epithelial cells, CD172a+ monocytic cells become infected with EHV-1 in the respiratory mucosa and transport the virus from the apical side of the epithelium to the lamina propria en route to the lymph and blood circulation. Whether CD172a+ monocytic cells are specifically recruited to the infection sites in order to pick up virus is unknown. In our study, equine nasal mucosa explants were inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…The shedding of atypical porcine pestivirus in urine and saliva is in line with other publications [ 8 , 15 ], but our study is the first report where a commercial viral swab was used. When more details of the shedding of APPV are identified, saliva sampling could in the future be an easy and cost-effective way to screen large groups of pigs for the virus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The shedding of atypical porcine pestivirus in urine and saliva is in line with other publications [ 8 , 15 ], but our study is the first report where a commercial viral swab was used. When more details of the shedding of APPV are identified, saliva sampling could in the future be an easy and cost-effective way to screen large groups of pigs for the virus.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in the experimental infections described above, splay leg was induced in 0–40% of the piglets born from the sows inoculated with APPV [ 7 , 8 ]. This prevalence was an unusual observation of splay leg since the syndrome typically occurs only as sporadic cases [ 21 ], whereas congenital tremor commonly causes distinct, high-morbidity outbreaks [ 2 , 15 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the abortigenic strains recruit fewer leukocytes into the URT, which enables the virus to replicate in the respiratory epithelium to promote viral shedding. Occupant immune cells become infected with abortigenic EHV1 in a less explosive and more controlled manner, followed by a silent transport in these “Trojan horses” to the pregnant uterus (Vandekerckhove et al, 2010 ; Laval et al, 2015 ; Zhao et al, 2017 ). In general, our findings support the speculation that the abortigenic variants may have a selective advantage over the neurovirulent variants for long-term maintenance within the equine population, by mastering the antiviral effect of IFN at the URT (Nugent et al, 2006 ; Goodman et al, 2007 ; Vandekerckhove et al, 2010 ; Laval et al, 2015 ; Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary respiratory epithelial cells inoculated with the neurotropic Ab4 strain showed an up-regulation of mRNA expression of IFNα, which indicates the activation of the IFN response in the URT (Soboll Hussey et al, 2014 ). Intriguingly, recent studies of the URT demonstrated that chemokine expression varied between abortigenic and neurovirulent EHV1 strains in vivo and ex vivo (Holz et al, 2017 ; Zhao et al, 2017 ). A careful analysis of the early IFN response against EHV1 at the URT, and a comparison between abortigenic and neurovirulent variants may contribute to our understanding of the invasion kinetics of the two types of EHV1 in the URT.…”
Section: Introductionmentioning
confidence: 99%
“…The process of cell-to-cell virus transfer from infected epithelial cells to PBMC is relatively simple. EHV-1 undergoes full replication cycles in the epithelium and the released infectious virus particles result in dendritic cell infection [ 81 , 82 , 83 ]. Since the mutant viruses can replicate to levels comparable to parental viruses ( Figure 2 A–C), it was not surprising to see no effect on virus spread between epithelial cells and PBMC.…”
Section: Discussionmentioning
confidence: 99%